Rapid Actions of the Nuclear Progesterone Receptor through cSrc in Cancer - Claudia Bello-Alvarez; Carmen J. Zamora-Sánchez; Ignacio Camacho-Arroyo (Cells, 2022)
The nuclear progesterone receptor (PR) is mainly known for its role as a ligand-regulated transcription factor. However, in the last ten years, this receptor’s extranuclear or rapid actions have gained importance in the context of physiological and pathophysiological conditions such as cancer. The PR’s polyproline (PXPP) motif allows protein–protein interaction through SH3 domains of several cytoplasmatic proteins, including the Src family kinases (SFKs). Among members of this family, cSrc is the most well-characterized protein in the scenario of rapid actions of the PR in cancer. Studies in breast cancer have provided the most detailed information on the signaling and effects triggered by the cSrc–PR interaction. Nevertheless, the study of this phenomenon and its consequences has been underestimated in other types of malignancies, especially those not associated with the reproductive system, such as glioblastomas (GBs). This review will provide a detailed analysis of the impact of the PR–cSrc interplay in the progression of some non-reproductive cancers, particularly, in GBs.